THE INFLUENCE OF EMPLOYEE LEADERSHIP AND EMPOWERMENT ON THE PERFORMANCE OF PENDERES EMPLOYEES WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (Case Study: Kebun Tanah Raja PTPN III) - Arga Malona; Yusniar Lubis; Syaifuddin Syaifuddin (SEAN Institute, 2023)
This study aims to examine the impact of leadership and coercion of workers on the achievement of incised workers with worker motivation as an intervening agent at PTPN III Kebun Tanah Raja This research will be carried out at PTPN III Kebun Tanah Raja which is located in the Region. Pls. Mengkudu, North Sumatra, this study took place from August 2022 until the end of this study the population consisted of 127 PTPN III Kebun Tanah Raja incisors, the sample used in this study was a permanent swamp sample where all 127 people were sampled, the technique The data analysis used in this study is the path analysis technique. For the results of this study, leadership affects the performance of PTPN III's Tanah Raja field workers. The bullying of the workers reflected the achievements of PTPN III's Tanah Raja field workers. Work motivation affects the performance of PTPN III's Tanah Raja field workers. Leadership affects the work motivation of PTPN III's Tanah Raja field workers. Worker harassment affects the work motivation of PTPN III's Tanah Raja field workers. Leadership influences worker performance through motivation in Taman Tanah Raja. Worker empowerment affects worker performance through motivation in Taman Tanah Diraja. Keywords: Leadership, Empowerment, Motivation, and Performance